INTERLANGUAGE CONCERNING FOSSILIZATION AND UNIVERSAL GRAMMAR: A LITERATURE REVIEW ON SECOND AND FOREIGN LANGUAGE ACQUISITION - Salma Mu’min Shiddiq; Lulud Oktaviani (Journal of English for Academic and Specific Purposes (JEASP), 2022)
The phenomenon of fossilization as the feature of interlanguage has been acknowledged and studied many times since the emergence of the theory proposed by Selinker which came into existence in the field of SLA in 1972. The premise of interlanguage as a separate language system used by second language learners as well as foreign language learners in learning their target language is credited to Selinker. Fossilization in interlanguage is coined by Selinker and is generally defined as a cessation of learning the target language. Nevertheless, the notion that interlanguage is fossilized is still open to question. Thus, this present study aims to provide insight to the reader about the concept of fossilization by defining and characterizing interlanguage and fossilization in second and foreign language acquisition, discussing the causes of fossilization in interlanguage development, as well as examining the relationship between interlanguage development and Universal Grammar principle in an attempt to help the reader better grasp and comprehend the phenomenon.